LO083: Outcomes and resource utilization among syncope patients transported by emergency medical services. (2nd June 2016) - Yau, L.; Mukarram, M.A.; Kim, S.; Arcot, K.; Thavorn, K.; Taljaard, M.; Sivilotti, M.; Rowe, B.H.; Thiruganasambandamoorthy, V.
Abstract : Introduction: Syncope accounts for 1% of all annual emergency department (ED) visits in Canada with only 10.3% suffering serious adverse event (SAE) within 30-days. However, 66% are transported to ED by Emergency Medical Services (EMS). Our objectives were to assess 30 day SAE among syncope patients transported by Emergency medical services (EMS), assess the need to develop an EMS clinical decision aid, and estimate anticipated health care savings by diverting patients from the ED to alternative care pathways.Methods: We conducted a prospective cohort study at four tertiary care EDs from Feb 2012 to Feb 2013. We included patients ≥16 years of age with syncope and who arrived to the ED via EMS. We collected patient demographics, medical history, 30 day SAE, EMS time points (call received, EMS arrival on scene, EMS departure from scene, time of transfer of care in the ED), critical EMS interventions, and ED length of stay. We assessed for the occurrence of any SAE (death, arrhythmia, other cardiac and non-cardiac conditions) within 30 days of ED disposition. We used descriptive analysis, unpaired two-tailed t-test and chi-square test. Ethics approval was obtained at all study sites.Results: Of 1, 475 ED patients with syncope during the study period, 992 (67.3%) arrived by EMS. Mean times (SD) for EMS arrival to the scene, patient assessment at the scene and transfer of patient from scene to the ED were 10.1 (6.4), 18.9 (8.3), and 14.6 (11.5) minutes respectively. Only two patients had critical interventions enroute (pacing and defibrillation). Overall 138 (13.9%) patients suffered a SAE; 32 (3.2%) detected by EMS, 58 (5.8%) detected during ED evaluation, 48 (4.8%) after ED disposition. The average ED length of stay was 5.9(4.2) hours. Based on average of cost from two sites, we estimated that total cost of transporting syncope patients from the scene to the ED to be 4 million in Canada. The total cost of ED care for syncope patients transported by EMS in Canada was calculated at 21.5 million.Conclusion: A substantial proportion of patients arriving to the ED via EMS suffer no SAE within 30 days. Correspondingly, our results suggest a need for an EMS clinical decision aid to divert low-risk syncope patients to alternative care pathways such as family physicians or rapid access clinics. If developed and implemented, this tool can potentially reduce EMS burden, ED crowding, and reduce healthcare costs.